Desenvolvimento de inversor multifásico baseado em semicondutores de carbeto de silício para tração automotiva - Silva, Eduardo Cattani (2024)
In this dissertation, the design and implementation of a pentaphase inverter using silicon carbide semiconductor switches intended for automotive traction are carried out. This converter operates with a nominal bus of 400 V, supplied by the vehicle’s batteries, processing a maximum power of 123.5 kVA. Initially, a literature review is conducted on the challenges and solutions surrounding the operation of electric motors for electric vehicle traction, with an emphasis on semiconductor technologies and converter topologies. In the sequence, the study and sizing of the power semiconductor switches and the appropriate capacitive bank for operation under the project’s conditions are carried out, based on mathematical analyses and computational simulations. Furthermore, the principles and organization of the printed circuit board design used in the inverter’s power processing are addressed and discussed. The following design topics cover aspects of the drive, from protection circuits to operation diagnostics, with the aim of ensuring proper and safe activation of the semiconductor switches. Finally, a series of tests are conducted to assess the safety and operational capacity of the designed inverter, the results of which validate its development.